En æstetisk filosofi om sanseoverskridende erfaringer - Albinus, Lars (Dansk Teologisk Tidsskrift, 2014)
The full doctoral thesis, The Beautiful Thinking, by the Danish Historian of Ideas Dorthe Jørgensen, is an impressive and erudite work that challenges modern theology to learn from philosophical aesthetics or, more specifically, a ‘metaphysics of experience’. Taking her point of departure in Baumgarten’s concept of sensitive cognition, she sets out to develop a philosophy which, contrary to the erratic strictures of empirical science, on the one hand, and superficial tendencies of the modern entertainment culture, on the other, is able to grasp experiences of ‘immanent transcendence’ or ‘a surplus of meaning’. In this review article, however, I warn against the romanticizing implications of this endeavor inasmuch as the subject matter of theology is a confessional tradition rather than some form of experiential sensitivity.